Media Sosial sebagai Ruang Digital Activism Generasi Muda Dalam Memperjuangkan Isu Lingkungan - Laras Ayu Andini (Jayapangus Press, 2025)
Environmental issues are among the most pressing challenges in Indonesia, ranging from waste management and air and water pollution to deforestation. However, studies that specifically examine how young people articulate environmental concerns through social media and how this influences their political preferences remain limited. This study seeks to address this gap by analyzing the role of social media as a space for digital activism among youth. The research employed a descriptive qualitative approach with participants drawn from young voters aged 17–30 years who actively use Instagram and Twitter/X, and who have previously engaged in discussions about environmental issues on social media. Data was collected through in-depth interviews and analyzed using a thematic approach. The findings indicate that Instagram plays a greater role in fostering emotional awareness through visual content, while Twitter/X is more often utilized for critical discussions and political mobilization. Together, these platforms form a digital public sphere that enables young people not only to increase their environmental awareness but also to articulate it as part of their political considerations. These findings highlight that digital activism on environmental issues can serve as a strategic factor in shaping the political preferences of young people in Indonesia.